2014
DOI: 10.2174/1871528112666131219163405
|View full text |Cite
|
Sign up to set email alerts
|

The Alzheimer Pandemic: Is Paracetamol to Blame?

Abstract: Historical Background: The clinical recognition of a form of dementia closely resembling Alzheimer's disease dates from around 1800. The role of analgesics derived from coal-tar in the spread of the pandemic is traced in terms of the introduction of phenacetin (PN) in 1887; its nephrotoxicity; the observation of lesions characteristic of the disease by Fischer and Alzheimer; the discovery of paracetamol (PA) as the major metabolite of PN; the linking of kidney injury and dementia with high PN usage; and the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 120 publications
(302 reference statements)
0
4
0
Order By: Relevance
“…Oxidative stress has been linked to the neuronal cell death since long. The induction of nitric oxide (NO) produced by nitric oxide synthase (NOS) has been found to play a role in oxidative damage linked to neurodegeneration [86]. Pro-inflammatory cytokines have been found responsible for neuroinflammation leading to neurodegeneration of which TNF-α tops the list [87].…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress has been linked to the neuronal cell death since long. The induction of nitric oxide (NO) produced by nitric oxide synthase (NOS) has been found to play a role in oxidative damage linked to neurodegeneration [86]. Pro-inflammatory cytokines have been found responsible for neuroinflammation leading to neurodegeneration of which TNF-α tops the list [87].…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with those previously published, showing a protective effect of NSAIDs against dementia (Szekely et al, 2008). Likewise for paracetamol (Jones, 2014) and opioids (Dublin et al, 2015), which were shown to be risk factors for the development of dementia. Unfortunately, our results are only exploratory, the low prescription rate of several drugs did not allow us to assess precisely and reliably the correlation with the presence of ADRD for each pain medication.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding paracetamol, our results should be taken with caution. To date, there is no reliable study showing a link between paracetamol consumption and the development of cognitive disorders (Jones, 2014). Moreover, the difficulty in separating the effect of pain from the effect of its treatment makes the interpretation of such exploratory results even more complicated.…”
Section: Discussionmentioning
confidence: 99%
“…This again shows that ‘historical’ drugs may yield surprising and dangerous effects and we should not trust that old means safe. Nevertheless, relating the ubiquitous paracetamol (Modick et al., ) to the worldwide increase of Alzheimer's disease (Jones, ) appears somewhat far‐fetched.…”
Section: Not Approvable?mentioning
confidence: 99%